Friction in fiction: A study of the importance of open problems for literary conversations - Sønneland, Margrethe (L1-Educational Studies in Language and Literature, 2019)
The present paper is part of a multiple case study of literary classroom work at Norwegian lower-secondary schools (students aged 13–16) where three classes are invited to discuss texts presented to them as open problems. The first case study carried out showed that the text and the task had the power to attract as well as the ability to generate student engagement. The second case study identified varia-tion in student engagement based on a description of intensity and an analysis of students' discursive valuation mechanisms. Following those findings of engagement, there is a need to understand what it is about the three short stories involved―Raymond Carver's Little Things (Carver, 2004), Roy Jacobsen's Run for Your Life (Jacobsen, 2001) and Franz Kafka's Before the Law (Kafka, 2000b)―that may yield that engagement. The main finding made is that what attracts students' attention are different forms of friction that delays the unfolding of the motif or plot of the story. This friction can therefore also be seen as the basis for the engagement shown by students in conversations. The findings suggest that lower-secondary students take an approach characterized by substantial engagement to those aspects of the text that represent problems of high relevance even within the field of literary studies. At a general level, the findings of the study open up for a discussion about whether greater use should be made of the genuine problems of literary studies in order to create student engagement.